Black carbon in Xiamen, China: Temporal variations, transport pathways and impacts of synoptic circulation. (February 2020) - Deng, Junjun; Zhao, Wei; Wu, Libin; Hu, Wei; Ren, Lujie; Wang, Xin; Fu, Pingqing
Abstract: Black carbon (BC) plays a vital role in atmospheric environment and climate change. Temporal variations and transport pathways of BC in Xiamen, China with the impacts of synoptic circulation were investigated in 2014 with Aethalometer. Annual mean BC concentration was 4270 ng m −3 . BC exhibited clear diurnal (seasonal) variations, with the maximum of 6182 (4755) ng m −3 at 6:00 (in spring) and minimum of 2847 (3774) ng m −3 at 13:00 (in summer). Conditional probability function analysis indicated that high BC concentrations were associated with northwesterly winds with low wind speed. Air masses originating from the East China Sea and passing along with East China Coast had the highest BC concentrations. Potential source contribution function and concentration weighted trajectory analysis suggested that major sources for BC included the surrounding region, southwestern Fujian and eastern Guangdong to the southwest, Hubei, Hunan and Jiangxi to the northwest, the East China Sea and the South China Sea. Of the nine synoptic circulation patterns, three cyclone-related patterns were associated with low BC concentrations and small biomass burning (BCbb ) contributions. Of the six anticyclone-related patterns, the three cold-high circulations around winter were associated with moderate BC concentrations and large BCbb contributions. The two cold-high patterns in spring and autumn were associated with high BC concentrations and small BCbb contributions, while the warm-high pattern was associated with moderate BC concentration and small BCbb contribution. The findings provide insights into the transport mechanisms of BC with the impacts of synoptic pattern in China. Highlights: One year on-line observation of BC was conducted in Western Taiwan Strait in China. Originations and transport pathways of BC were investigated with CPF, PSCF and CWT. Impacts of synoptic circulations on BC from different source sectors were analyzed.